2022
DOI: 10.1038/s42949-022-00077-7
|View full text |Cite
|
Sign up to set email alerts
|

A trait-based conceptual framework to examine urban biodiversity, socio-ecological filters, and ecosystem services linkages

Abstract: Maximizing the functional performance of urban green infrastructure is important to deliver critical ecosystem services that support human well-being. However, urban ecosystems are impacted by social and ecological filters that affect biodiversity, shaping how species’ traits are functionally expressed, thus affecting ecosystem services supply. Our Social–Ecological Traits Framework addresses the impacts of socio-ecological systems on the phenotypic expression of traits and ecosystem services delivery. This fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For example, expanding work around functional species traits position them as both a way for assessing the functional implications of different community assemblages and as a connector between biodiversity and people (e.g. de Bello et al 2010 ; Andersson et al 2021c ; Grilo et al 2022 ). Regional and global initiatives for compiling and cataloguing traits information (e.g.…”
Section: Expanded Contextualisation and Methodological Approachesmentioning
confidence: 99%
“…For example, expanding work around functional species traits position them as both a way for assessing the functional implications of different community assemblages and as a connector between biodiversity and people (e.g. de Bello et al 2010 ; Andersson et al 2021c ; Grilo et al 2022 ). Regional and global initiatives for compiling and cataloguing traits information (e.g.…”
Section: Expanded Contextualisation and Methodological Approachesmentioning
confidence: 99%
“…Urban systems present an opportunity to test and apply a range of ecological theories and concepts that have emerged from work in natural systems, such as trait frameworks, metapopulation theory and biodiversity–ecosystem function links (e.g., Aronson et al, 2016; Grilo et al, 2022). Urban areas encompass a range of interlinked ecosystems, and more work is needed to understand how ecological patterns and processes vary among urban environments and when compared with natural systems and how urban patterns may scale up to macroecological processes (Hahs & Evans, 2015; Lokatis et al, 2023).…”
Section: Priorities For Urban Insect Ecology Research and Conservationmentioning
confidence: 99%
“…This may be attributed to Hefei's recent significant efforts in ecological civilization construction and green development strategy. A study by Grilo et al showed that urban green spaces not only provide important cultural services for urban residents but also play a crucial role in maintaining urban biodiversity and ecosystem functions [32]. Therefore, strengthening urban green space construction is an important approach to reconcile the conflict between urban development and ecological protection.…”
Section: Impacts Of Urbanization On Esvmentioning
confidence: 99%